Morpho-Semantic Analysis of Word Formation in Abraham Lincoln’s “The Gettysburg Address” - Yulius Yosef Kasimo; Yuliana M. D' Karmel Kara (The Study Program of English Education of Palangka Raya University, 2026)
This research analyzes word formation, including inflection, derivation, grammatical meaning, lexical meaning, contextual meaning. This research employed a qualitative approach supported by morphological and semantic theory. The study focuses on Abraham Lincoln's